Concise Review: In Search of Unlimited Sources of Functional Human Pancreatic Beta Cells. (19th December 2012) - Scharfmann, Raphael; Rachdi, Latif; Ravassard, Philippe
Abstract : Rodent and human beta cells are not identical, and knowledge of human beta cells has not progressed as quickly as understanding of rodent beta cells because of the difficulty of accessing unlimited sources of functional human pancreatic beta cells. The main focus of this review concerns recent strategies to generate new sources of human pancreatic beta cells. This knowledge would provide a strong basis for developing new treatments for diabetic patients. Abstract : It is well‐established that insulin‐producing pancreatic beta cells are central in diabetes. In type 1 diabetes, beta cells are destroyed by an autoimmune mechanism, whereas in type 2 diabetes, there is a decrease in functional beta‐cell mass. In this context, studying beta cells is of major importance. Beta cells represent only 1% of total pancreatic cells and are found dispersed in the pancreatic gland. During the past decades, many tools and approaches have been developed to study rodent beta cells that efficiently pushed the field forward. However, rodent and human beta cells are not identical, and our knowledge of human beta cells has not progressed as quickly as our understanding of rodent beta cells. We believe that one of the reasons for this inefficient progress is the difficulty of accessing unlimited sources of functional human pancreatic beta cells. The main focus of this review concerns recent strategies to generate new sources of human pancreatic beta cells.